Letter - Winstanley, E.
029-0038-001 Telegraphic address: Inland - "Wholesale Manchester" Foreign - "COPEXPORT. Manchester" Telephone: Blackfriars 1212 Extension No. Please address your reply: Co-operative Wholesale Society Limited. Exporters, Buying and Shipping Agents, 1, Balloon Street, Manchester, 4. Cable Codes: A.B.C., 6th and 7th editions; Western Union 5 letter; Bentley Complete Phrase; Bentley Second Phrase; A.1. MARCONI, and Private. Our reference EXPORT ST/HP. 345 Your reference 18th January, 1938. The Trades Union Congress General Council, Transport House, Smith Square, London. Dear Sirs, We thank you for your letter of yesterday's date reference HVT/FC/165 together with your cheque amounting to £2050.11.10. in settlement of our invoices of the 8th and 13th instant, amounting to £211.1.0., £64.0.0. £1771.7.4. and £4.3.6. Our official receipt is attached hereto. In regard to further consignments, we look forward to receiving any information you may obtain from the International Solidarity Fund, Paris. Meanwhile, we remain, Yours faithfully, E. Winstanley Export Department. 292/946/29/38